Study of breakdown occurrence on the 11kV sewerage plant substation in UiTM Shah Alam / Muhammad Syahmi Abd Razak - Abd Razak, Muhammad Syahmi (2014)
This paper describes the characteristics of environment of llkV outdoor distribution substation that was affected to underground cable supply. There is some visual checking and site testing to detect breakdown on the cable and calculated cost involve comparing to suggested solution. The cause of breakdown must be effectively found so that further solution could be decide in order to minimize any spending cost on substation maintenance. The main course that seriously studies in this case is the effect of moisture to the 1 IkV substation. The effect of moisture could cause faulty which are not be able to confirm and standardize its characteristics at any different place or case.